The Effect of EFL Teachers’ Stress on their Classroom Management Practices: An Investigation of Male and Female Teachers - Alipour, Hossein; Safaie, Ebrahim (IJRDO- Journal of Educational Research, 2018)
The present study was conducted to investigate the relationship between perceived stress and behavior and instructional management in male and female foreign language teachers in cities of Mohr, Lamerd, Parsian and Asalouye. A total of 96 male (N = 58) and female (N = 38) university and high school teachers participated in the present study. All participants were randomly selected from different universities and high schools which were more accessible and accommodating for the purpose of study. Behavior and Instructional Management Scale (BIMS) developed by Wolfgang and Glikman (1986) was used to collect data about teachers’ reported classroom management practices. The Perceived Stress Scale (PSS) developed by Cohen, Kamarck, and Mermelstein (1983) was used for measuring the perception of stress. The reliability and validity of the questionnaires were found acceptable according to Cronbach’s Alpha and factor analysis. Questionnaires were administered to the teachers via emails and in person. The results obtained from the Pearson correlation analyses revealed that there was not a significant relationship between perceived stress and behavior management in both male and female teachers, reflecting the fact that high stress was unlikely to affect behavior management in both genders. For instructional management, it is likely for both male and female teachers to decrease their instructional management practices when their perceived stress is high. The implications of the findings are discussed.